2013
DOI: 10.1148/rg.336125162
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging–guided Focused Ultrasound for Treatment of Bone Metastasis

Abstract: Magnetic resonance (MR) imaging-guided focused ultrasound is an alternative noninvasive method for reducing the pain in skeletal metastases. MR imaging-guided focused ultrasound ablation offers several key advantages over other noninvasive treatment modalities. This technology enables the performance of three-dimensional treatment planning with MR imaging and continuous temperature mapping of treated tissue by using MR thermometry, thereby enabling real-time monitoring of thermal damage in the target zone. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 27 publications
(34 reference statements)
2
98
0
10
Order By: Relevance
“…Details on treatment planning of image-guided FUS are outside the scope of this review, and can be found elsewhere for MRgFUS [16] and USgFUS [33].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details on treatment planning of image-guided FUS are outside the scope of this review, and can be found elsewhere for MRgFUS [16] and USgFUS [33].…”
Section: Resultsmentioning
confidence: 99%
“…Attenuation of ultrasound energy as it propagates through biologic tissue results in a rise of temperature in the treated volume. Coagulative necrosis and cell death occur within seconds at temperatures in the range of 65-85°C [16], so that the ablative treatment must be well localized to the tumor target and avoid surrounding normal tissues. To achieve the required focusing and rapid elevation of tissue temperature at depth, the ultrasound energy is usually intensified at a focal spot by using multiple intersecting ultrasound beams that converge on the target.…”
Section: High-intensity Focused Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…75 MRgFUS has been first proposed with a potential in pain palliation of bone metastases, for its good results in patients non-responding to radiotherapy while applying acoustic energy on the bone surface resulting in bone cortex heating, and indirectly ablating the adjacent periosteum-the most innervated component of mature bone tissue, and tumour tissue, and a major source of pain. 11,76 The bone is a common site for metastasis. The primary cancers that most frequently metastasize to bone are breast and prostate cancers (post-mortem incidence of bone metastases: breast 73%, prostate 68%, thyroid 42%, lung 36%, renal 35%), and these are among the most incident and curable worldwide.…”
Section: Mrgfus Target and Applications In Musculoskeletal Pathologymentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Conversely, benign diseases are still under investigation and, so far, the treatment of only osteoid osteoma has appeared in literature. [12][13][14][15] There is scarce literature describing the characteristics and the treatment of benign lesions other than osteoid osteoma, 16 and the studies are usually restricted to a low number of patients.…”
Section: Introductionmentioning
confidence: 99%